A Typology of Guanxi-Based Governance Mechanisms for Knowledge Transfer in Business Networks of Chinese Small and Medium-Sized Enterprises. (August 2017) - Ko, Wai Wai; Liu, Gordon
Guanxi has strong implications for interactions among individuals in Chinese society. This study investigates guanxi-based governance mechanisms in the context of knowledge transfer among Chinese small and medium-sized manufacturing firms. We analyze, in-depth, qualitative interview data gathered from 78 Chinese engineers who work for Chinese small and medium-sized die-casting manufacturers. Our findings reveal that guanxi influences the production of three forms of guanxi-enabled trust: guanxi-enabled relational trust, calculative trust, and institutional trust. By combining these forms of trust, we generate a typology of seven guanxi-based governance mechanisms for knowledge transfer—"guanxi-hu, " "huibao, " "lun, " "gan-qing, " "jiao-qing, " "ren-qing, " and "mianzi." We discuss the research and managerial implications of our findings.